1996
DOI: 10.1177/009365096023003004
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of International News Flow

Abstract: This research examines the structure of international news flow and its determinants, using network analysis. International newspaper and periodicals trade data in Commodity Trade Statistics published by the United Nations are used to describe the international news flow network. NEGOPY reveals the inequality of international news flow between the core and the periphery. The Western industrialized countries are at the center, dominating international news flow. Cluster analysis reveals that the international n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
2
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 40 publications
8
101
2
4
Order By: Relevance
“…First, population size is strongly and positively associated with news coverage, with more populous countries receiving more mentions in the news; replicating some previous findings (Dupree, 1971;Charles et al, 1979;Ishii 1996). GDP is found to have a positive correlation, however the p-value is above the conventional cut-off for statistical significance, thus providing no real support for previous findings (Kim and Barnett, 1996;Golan, 2008). Volume of trade with the UK and distance from the UK were also not found to have any effect, despite strong findings in previous research.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…First, population size is strongly and positively associated with news coverage, with more populous countries receiving more mentions in the news; replicating some previous findings (Dupree, 1971;Charles et al, 1979;Ishii 1996). GDP is found to have a positive correlation, however the p-value is above the conventional cut-off for statistical significance, thus providing no real support for previous findings (Kim and Barnett, 1996;Golan, 2008). Volume of trade with the UK and distance from the UK were also not found to have any effect, despite strong findings in previous research.…”
Section: Discussioncontrasting
confidence: 65%
“…This finding was replicated in a later study which also encompassed news websites (Wu, 2007). A country's economic development can also be an influential factor: Golan's (2008) analysis of US television found that, as well as trade, national GDP can predict coverage of African countries, while Kim and Barnett's (1996) analysis of international newspaper trade data found economic development to be the most significant of a host of contextual factors.…”
Section: Theorizing International Outlinking Patternsmentioning
confidence: 84%
“…The structure of the network reveals the current geopolitical power dynamics. For example, using Internet bandwidth capacity, hyperlink connections, website use, and website ownership as proxy measures, Barnett and his colleagues showed a core-peripheral structure (Barnett, 2001;Kim & Barnett, 1996;Barnett & Park, 2014;Ruiz & Barnett, 2014;Barnett, Ruiz, Xu, Park, & Park, 2016). They concluded that the globalized cyberspace is characterized by an unequal exchange between powerful information rich and information poor countries, which has led researchers to question whether cyberspace is truly boundary-less and independent from the geopolitical reality on the ground.…”
Section: Applying Network Analysis To International Relationsmentioning
confidence: 99%
“…Also, the typical structure of egocentric network data provides one of the ideal cases for reliably estimating multilevel mediation effects since a large number of focal survey respondents serving as upper-level observations. Although I ground this work within this specific setting, the general approach advanced in the present article can be easily extended and applied to other substantive domains of interest, such as organizational communication (e.g., Feeley & Barnett, 1997;Monge & Contractor, 2003), international/intercultural communication (e.g., Kim & Barnett, 1996), contextual influences in interpersonal, or mass communication processes (e.g., Kim et al, 2013;Parks & Floyd, 1996) and to any research on networks and social media (e.g., Ellison, Steinfield, & Lampe, 2007), provided that the theoretical perspective and data structure follows a standard multilevel framework.…”
Section: A Mediation Analysis Using Multilevel Linear Modelsmentioning
confidence: 99%